2022
DOI: 10.3389/fonc.2022.878275
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Neoadjuvant Chemotherapy and Log Odds of Positive Lymph Nodes and Their Prognostic Role in Advanced Ovarian Cancer Patients With Optimal Cytoreductive Surgery

Abstract: PurposeTo analyze the relationship between neoadjuvant chemotherapy (NACT) and log odds of positive lymph nodes (LODDS), as well as their prognostic role in advanced ovarian cancer (AOC) patients with optimal cytoreductive surgery.Patients and MethodsFrom the SEER database during 2010-2016, we identified 1,012 AOC patients with optimal cytoreductive surgery. Univariable and multivariable logistic regression was performed to identify the relationship between NACT and LODDS. Overall survival (OS) and cancer-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Hence, reducing the mortality of these patients is key to reducing the overall mortality of ovarian cancer patients. At present, patients with stage III ovarian cancer are often treated with neoadjuvant chemotherapy combined with interval debulking surgery (2)(3)(4). Chemotherapy has a significant curative effect on multiple malignant tumors (5,6), and patients who achieve complete response after neoadjuvant chemotherapy have better outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, reducing the mortality of these patients is key to reducing the overall mortality of ovarian cancer patients. At present, patients with stage III ovarian cancer are often treated with neoadjuvant chemotherapy combined with interval debulking surgery (2)(3)(4). Chemotherapy has a significant curative effect on multiple malignant tumors (5,6), and patients who achieve complete response after neoadjuvant chemotherapy have better outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that the prognosis of patients with OC initially treated with NACT was not inferior to those treated with primary debulking surgery (PDS) [34,35]. Conversely, other studies have found no survival bene t or, in fact, an even worse prognosis in patients treated with NACT compared to PDS [36,37]. According to the primary treatment guidelines for OC developed by the Society of Gynecologic Oncology and the American Society of Clinical Oncologists, women with a high perioperative risk or a low likelihood of cytoreduction to residual lesions < 1 cm (ideally without signi cant lesions) should receive NACT [38].…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer (OC) is a common malignancy that ranks 1st among gynecologic cancers and 5th overall in the rate of cancer causing deaths in women [1]. In 2020, there were 313,959 new cases and 207,252 deaths as a result of OC in 185 countries worldwide, while 17.63% (55,342) of the global new cases, and 18.10% (37,519) of the global deaths were in China [2]. Due to the lack of effective screening methods and speci c symptoms, 60% of patients with OC are at an advanced stage at their rst diagnosis (34% in stage III or 26% in stage IV), even up to 80% of them with serous OC (51% in stage III or 29% in stage IV) [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies neither has a small sample size nor cover full aspects of ovarian cancer. Last but not least, the decision to perform lymphadenectomy was determined by the surgeon's discretion without any other objective criteria (23,24), or it depended on the policy of the hospital whether lymph node excision was performed (25).…”
Section: Discussionmentioning
confidence: 99%